Developmental changes in the architecture of umbilical artery of goat (Capra hircus) - VAISH, RAKHI; PARMAR, M L; MALIK, M R; TALUJA, J S (The Indian Journal of Animal Sciences, 2014)
Developmental changes of umbilical artery on 30 goats were studied in prenatal, neonatal and adult life. The diameter and CS area of the vessel gradually increased in groups 1 to 3, and thereafter decreased in group 4 and ultimately obliterated in group 5. Among the tunics, the tunica adventitia was thickest (88. 15Âµm) in group 1. However, tunica media was thickest in other groups. The sum of the percentage increase of thickness of total wall and its different tunics in early stage of gestation was about 40 times (1790%) in comparison to the corresponding value (45%) in late. The total wall thickness and thickness of tunica media decreased (-30%) and (-49%), respectively, from neonatal to adult goat. Weak to moderate PAS positive substances were observed in tunica intima anel tunica media in contrast t intense reaction in tunica adventitia.